Catalytic microgelators for decoupled control of gelation rate and rigidity of the biological gels - Hong, Yu-Tong; Bregante, Daniel T.; Lee, Johnny Ching-Wei; Seo, Yongbeom; Kim, Dae-Hyun; Lee, Yong Jae; Schook, Lawrence B.; Jeon, Hojeong; Sung, Hak-Joon; Flaherty, David W.; Rogers, Simon A.; Kong, Hyunjoon (Elsevier BV, 2020)
Fibrin gels have been extensively used for three-dimensional cell culture, bleeding control, and molecular and cell therapies because the fibrous networks facilitate biomolecular and cell transport. However, a small window for gelation makes it difficult to handle the gels for desired preparation and transport. Several methods developed to control gelation rates often alter the microstructure, thereby affecting the mechanical response. We hypothesized that a particle designed to discharge thrombin cargos in response to an external stimulus, such as H2O2, would provide control of the gelation rate over a broad range while strengthening the gel. We examined this hypothesis by assembling poly (lactic-co-glycolic acid) (PLGA) particles loaded with thrombin and MnO2 nanosheets that decompose H2O2 to O-2 gas. The resulting particles named as catalytic microgelator were mixed with fibrinogen solution or blood containing 0.2 mM H2O2. Due to the increased internal pressure, these particles released a 3-fold larger mass of thrombin than PLGA particles loaded only with thrombin. As a consequence, catalytic microgelators increased the gelation time by one order of magnitude and the elastic modulus by a factor of two compared with the fibrin gel formed by directly mixing fibrinogen and thrombin in solution. These catalytic microgelators also served to clot blood, unlike PLGA particles loaded with thrombin. The resulting blood clot was also more rigid than the blood clot formed by thrombin solution. The results of this study would serve as a new paradigm in controlling gelation kinetics of pre-gel solution and mechanical properties of the post-gel matrix.